Cutaneous nerve fields of the anteromedial lower limb—Determination with selective ultrasound‐guided nerve blockade. Issue 1 (29th February 2020) - Riegler, Georg; Pivec, Christopher; Jengojan, Suren; Mayer, Johannes A.; Schellen, Christoph; Trattnig, Siegfried; Bodner, Gerd
Abstract: Background: This study aimed to determine the peripheral cutaneous nerve fields (CNF), their variability, and potential overlap by selectively blocking the intermediate (IFCN) and medial (MFCN) femoral cutaneous nerves and the infrapatellar branch of the saphenous nerve (IPBSN) in healthy volunteers. Methods: In this prospective study, ultrasound‐guided nerve blockades of the IFCN, MFCN, and IPBSN in 14 healthy volunteers were administered. High‐frequency probes (15–22 MHz) and 1 ml of 1% lidocaine per nerve were used. The area of sensory loss was determined using a pinprick, and all fields were drawn on volunteers' skin. A three‐dimensional (3D) scan of all lower limbs was obtained and the three CNF and their potential overlap were measured. Results: The mean size of innervation areas showed a high variability of peripheral CNF, with 258.58 ± 148.26 mm 2 (95% CI, 169–348.18 mm 2 ) for the IFCN, 193.26 ± 72.08 mm 2 (95% CI, 124.45–262.08 mm 2 ) for the MFCN, and 166.78 ± 121.30 mm 2 (95% CI, 94.1–239.46 mm 2 ) for the IPBSN. In 11 volunteers, we could evaluate an overlap between the IFCN and MFCN (range, 4.11–139.68 ± 42.70 mm 2 ), and, in 10 volunteers, between the MFCN and IPBSN (range, 11.12–224.95 ± 79.61 mm 2 ). In only three volunteers was an overlap area found between the IFCN and IPBSN (range, 7.46–224.95 ± 88.88 mm 2 ). The 3D‐scans confirmed the high variability of the peripheral CNF. Conclusions: Our study successfully determined CNF, their variability, and the overlap of the MFCN, IFCN, and IPBSN in healthy volunteers. Therefore, we encourage physicians to use selective nerve blockades to correctly determine peripheral CNF at the anteromedial lower limb.